2023
DOI: 10.1101/2023.01.12.22280967
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnostic value of plasma microbial cell-free DNA sequencing in hematopoietic stem cell transplant recipients: A systematic review and meta-analysis

Abstract: Hematopoietic stem cell transplant (HSCT) recipients are at increased risk for a wide spectrum of infections, including opportunistic infections with atypical presentations. Diagnosis can be challenging and often requires extensive testing and invasive procedures. Sequencing of plasma microbial cell-free DNA (mcfDNA) allows non-invasive untargeted detections of human pathogens, making this modality appealing for this patient population. The purpose of this study was to perform a meta-analysis to evaluate the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…These studies have reported accuracy assessments on a microbe-by-microbe basis and have gone even further to report clinical validity as well. Six representative studies including 683 patients are summarized in Table S4 ( 8 , 11 , 12 , 14 , 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported accuracy assessments on a microbe-by-microbe basis and have gone even further to report clinical validity as well. Six representative studies including 683 patients are summarized in Table S4 ( 8 , 11 , 12 , 14 , 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%